Antiasthmatic Medicinal Plants of Tanzania: An Ethnomedicinal and Ethnopharmacological Review - David Sylvester Kacholi (The Scientific World Journal)
Traditional medicinal plants (TMPs) are a significant part of people’s quality of life, offering a natural substitute for modern drugs with numerous side effects. In Tanzania, data on antiasthmatic TMPs are highly fragmented. This review, a comprehensive compilation of ethnobotanical research evidence, aimed to provide a thorough understanding of TMPs used by the locals for asthma management and identify species that have already been investigated in preclinical studies. The review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. To gather relevant literature on antiasthmatic TMPs used by Tanzanians, a web search using electronic databases (Scopus, PubMed, ProQuest, Academic Library, Web of Science, SciFinder, Wiley Online Library, Google Scholar, ScienceDirect, and African Journals Online) was conducted. The scientific names were verified through the Plants of the World Online database, and the collected information was analysed for descriptive statistics using Microsoft Excel software. The ethnomedicinal information was obtained from 24 different articles. Microsoft Excel software was used to analyse the data using descriptive statistics. A total of 62 TMPs belonging to 33 families were identified. Species of the Fabaceae (14.5%) and Rubiaceae families (8.1%) are the most utilized. The analysis revealed that trees (42.0%) and leaves (40.0%) are the most utilized life forms and plant parts, respectively. Most plant materials (59.7%) used to make remedies were collected from the wild environment. Decoction (55.0%) is the dominant preparation method of remedies, and the majority (69.0%) were orally administered. Of the recorded TMPs, 22.6% had their in vivo antiasthmatic activity reported in the literature. The review also highlighted the strategic significance of preparations of remedies made from TMPs for discovering and developing new antiasthmatic drugs. However, the need to identify the molecular targets of action and toxicological aspects of the TMPs should be considered.